ChemInform Abstract: Heterogeneously Copper‐Catalyzed Oxidative Synthesis of Imidazo[1, 2‐a]pyridines using 2‐Aminopyridines and Ketones under Ligand‐ and Additive‐Free Conditions. Issue 6 (February 2015) - Meng, Xu; Wang, Yanmin; Yu, Chaoying; Zhao, Peiqing
Abstract CuCl2 supported on TiO2 nanopowder efficiently catalyzes the aerobic oxidative cyclization reaction of 2‐aminopyridine derivatives and ketones to give imidazopyridines.